Splenic devascularization can replace splenectomy during adult living donor liver transplantation – a historical cohort study. (1st March 2019) - Moon, Deok‐Bog; Lee, Sung‐Gyu; Hwang, Shin; Ahn, Chul‐Soo; Kim, Ki‐Hun; Ha, Tae‐Yong; Song, Gi‐Won; Jung, Dong‐Hwan; Park, Gil‐Chun; Yoon, Young‐In; Cho, Hwui‐Dong; Kwon, Jae‐Hyun; et al.
Summary: Simultaneous splenectomy (SSPX) in adult living donor liver transplantation (ALDLT) has definitely beneficial roles such as portal flow modulation in small‐for‐size graft and correction of hypersplenism‐related pancytopenia, and so on, but disastrous complications after SSPX often occur. For the first time, we devised unique and innovative splenic devascularization (SDV) procedure to alleviated untoward effects of SSPX but to maintain its benefits for the indicated patients. From April 2013 to December 2014, 520 recipients underwent ALDLT, and the SSPX and SDV were simultaneously performed in 62 (11.9%) and 61 (11.7%) patients, respectively. The most common indication was hypersplenism‐related pancytopenia ( n = 101), small‐for‐size graft ( n = 14), hepatitis C virus (HCV) ( n = 7), and splenic artery aneurysm ( n = 1). Postoperative small‐for‐size graft syndrome (SFSS) was absent in both SSPX and SDV, and preoperative pancytopenia was improved in both groups since postoperative 1 week, although SSPX was more substantial than SDV. Preoperative splenic volume (706.2 ± 282.9 ml) after SDV significantly decreased to 425.5 ± 204.4 ml on 1 month, respectively. In contrast to SDV, SSPX resulted in longer operation time and higher incidence of postoperative complications including mortality. In conclusion, SDV can replace SSPX during ALDLT without hampering its beneficial roles seriously, but get rid of splenectomy‐related lethal complication.